A mixed-methods study on the recruitment of patients from ethnic minority groups to clinical trials in a central London teaching hospital - Cecilia Vindrola-Padros; Katie Gilchrist; Stuart Braverman; Rumana Omar; Edward Merivale; Ambar Hussenbux; Sanjay Khanna; Patience Renias-Zuva; Nick McNally; Rosamund Yu (Contemporary Clinical Trials Communications)
Background/aims: Additional research is needed to fully understand barriers in recruitment to clinical trials and how these might affect different ethnic groups. The aim of this study was to explore the factors acting as barriers and facilitators in the process of recruiting patients to clinical trials in a UK (central London) teaching hospital, with a particular focus on patients from ethnic minority groups, and on areas where action could be taken. Methods: The study was designed as a mixed-methods study comprised of: 1) a quantitative workstream which explored variations in the ethnic and gender breakdown of people admitted to hospital relative to the demographic characteristics of patients enrolled into research studies at the hospital, and 2) a qualitative workstream which explored staff experiences of recruiting patients to clinical trials and patients’ experiences of being approached to take part in a clinical trial. The quantitative workstream provided the necessary context for the design of the qualitative workstream. Results: We found that the chances of being involved in research at the hospital were lower in all ethnic minority groups and lower amongst female patients. Some of the factors acting as barriers in trial participation included patients’ perceptions of clinical research as a form of experimental medicine that might have high risks, the role of family members in decision-making processes, and language barriers (where patients might not be fluent in English and the study information is not communicated in other languages). Potential strategies to address underrepresentation included the development of accessible information about research and how patient data are used, development of study materials in multiple languages and use of interpreters during the recruitment process, support for staff in involving family members in decision-making and a greater ethnic diversity within study teams. Conclusions: The under-representation of people from minority ethnic populations in clinical research remains a major challenge, impacting on the rigour and applicability of findings as well as implying some populations are missing out on the benefits of research. Study design needs to place greater emphasis on patient need and convenience and therefore to take greater account of the deterrent effect of financial and time burdens on trial participants. Recruiting sites and sponsors need to review the provision of interpreting and translation support for trials, including availability and cost to individual studies and staff confidence in reliability.